Strengthening Moderation of Islamic Education to Overcome Terrorism - Abdul Hadi; Khalis Kohari; Ifham Choli (Research Synergy Foundation, 2023)
This research aims to explain the moderation of Islamic education in the component of curriculum objectives. The global Covid-19 pandemic, which has made the world community damage their economic resources and life, has not reduced the series of attacks committed by terrorist groups in various parts of the world. On March 20, 2020, ISIS attacked seven countries; Egypt, Niger, Nigeria, Philippines, Somalia, and Yemen. The new paradigms of Islamic educational moderate curriculum will prevent the fundamentalism and terrorism which are increasingly prevalent in some Islamic educational institutions today. Because the weapon of security forces in counter-terrorism only kills terrorists but could not change their minds and behavior typically. In some schools, as reported by Islamic Research and Societies Centre Jakarta Islamic State University (2020) about the religious attitude of students towards intern and extern minorities group, noted: That 1 in 3 students of university Students was intolerant of religious practice. This research uses the qualitative method in a phenomenological variant to get the actual data from the informer's consciousness through observation and interviews with some structural employees and all religious teachers of Al- Azhar Islamic High School. The data analysis used Miles and Hiberman's approach, and its validation was technical triangulation. The researcher found the applied curriculum objectives at Al-Azhar Islamic High School either in educational objectives or its learning process as follows: 1. Mindset of integration 2. Religious and Smart attitude 3. Acting in good relations with others.